Intelligent Autonomy of UAVs advanced missions and future use - Bestaoui Sebbane, Yasmina (Chapman & Hall/CRC artificial intelligence and robotics, 2018)
This book is meant for both scientists and practitioners. For practitioners, it presents existing solutions that are categorized according to various missions: surveillance and reconnaissance, 3D mapping, urban monitoring, precision agriculture, forestry, disaster assessment and monitoring, security, industrial plant inspection, etc. For scientists, it provides an overview of generic robotic problems such as coverage and orienteering; deployment, patrolling and foraging; search, tracking, and surveillance.